725 Monthly Antibiotic Use in The Sheffield Children's Hospital ED: A Hospital-Based Clinical Audit. (4th May 2021) - Leong, W S; Gray, J; Rimmer, C
Abstract: Aim: To evaluate guideline compliance of antibiotics prescription in Emergency Department (ED). To improve documentation of antibiotic prescription. To highlight the need for good antibiotic stewardship. To optimise the use of antibiotics. Method: A cross-sectional, retrospective patient record review was conducted regarding antibiotic prescription over 1 month in Sheffield Children's Hospital ED. All antibiotic prescriptions over that period were collected. From the total number of prescriptions, a convenience sample of 100 prescriptions was selected to correlate their indications with local guidelines. Results: A total of 290 prescriptions for 310 antibiotics were collected. The most frequent antibiotic prescribed was Penicillin V (26.7%), followed by Amoxicillin (21.3%), Co-amoxiclav (20.3%), and Flucloxacillin (16.5%). From the convenience sample, 12 antibiotics were prescribed inappropriately, with the most frequent being Co-amoxiclav (41.7%), followed by Penicillin V (25%), Amoxicillin and Flucloxacillin (both 16.7%). Overall, there has been good stewardship of antibiotic use with 88% of antibiotic prescribing conducted appropriately as per ED guidelines. Conclusions: Antibiotic resistance is a growing concern, with one of the leading causes being inappropriate prescription of antibiotics. Adhering to local guidelines can help to prevent them from developing resistance. Adherence can be improved through induction and training of clinicians.